Facility location selection using complete and partial ranking MCDM methods. (4th February 2015) - Ray, Ankita; De, Arijit; Dan, Pranab Kr.
Location planning is one of the essential tasks for a manufacturing industry. There are various factors that influence the selection of the location for a plant or service facility. Multi criteria decision making (MCDM) analysis is an optimisation technique which is applied to identify the most preferred alternative under multiple criteria. In this paper, some MCDM methods such as TOPSIS, SAW, GRA and MOORA have been used to determine the best location. Finally, an outranking MCDM approach (ELECTRE–I) is applied to find an appropriate plant location. The applied complete ranking MCDM methods are considered as the criteria and the evaluated values are taken as the performance of the decision matrix. By using these elements the ELECTRE–I method has been applied. A numerical example is taken to demonstrate the procedural steps of MCDM methods for selecting the best alternative for service facility or factory location.